INVIVO PERFORMANCE OF CONJOINED COATING OF POLYSORBATE 80 AND PEG FOR LOPERAMIDE LIPOSOMES - A PROMISING APPROACH FOR BRAIN TARGETING. - PICHANDY MUHTU PRASANNA; I SARATH CHANDIRAN (International Journal of Pharma and Bio Sciences, 2016)
Loperamide Hydrochloride (Lp) acts on opiatic receptors but due to its impermeable through Blood Brain Barrier (BBB), it can produce only peripheral opiatic effects (antidiarheal) in gastrointestinal tract but not central antinociceptive activity and this is due to the efflux of Pglyco protein (Pgly) of BBB. An approach has been made for Lp to permeate through BBB using a lipid carrier (Liposomes) coated with conjoined coating of Polysorbate80 (PS80) which is a Pgly efflux inhibitor and Polyethylene Glycol 20000 (PEG) for enhancing liposome bioavailability. Lp loaded Conjoined coated Liposomes (CCLs) was evaluated for its central antinociceptive activity using animal tail flick study. Among the different coated CCLs, S2G2 showed a higher maximal possible response (MPR%) (66.3%± 2.44) but S0G0 (without coat) showed negligible or absence of any appreciable MPR%. Dose response study confirmed that 25 µg/Kg was the optimum Lp concentration for its MPR% in S2G2 . Histopathology study ensured absence of any neurotoxicity by S2G2.Results of our study proved that the conjoined coated liposomes S2G2 was found to be an efficient drug delivery for Lp than other CCLs to target brain producing central antinociceptive activity .